Genome-wide characterization of PEBP gene family in Perilla frutescens and PfFT1 promotes flowering time in Arabidopsis thaliana - Xu, Huaxiang; Guo, Xi; Hao, Youjin; Lu, Geng; Li, Dan; Lu, Junxing; Zhang, Tao (Frontiers in Plant Science, 2022)
Phosphatidylethanolamine-binding proteins (PEBP) family plays important roles in regulating plant flowering time and morphogenesis. However, geneme-wide identification and functional analysis of PEBP genes in the rigorous short-day plant Perilla frutescens (PfPEBP) have not been studied. In this study, 10 PfPEBP were identified and divided into three subfamilies based on their phylogenetic relationships: FT-like, TFL1-like and MFT-like. Gene structure analysis showed that all PfPEBP genes contain 4 exons and 3 introns. Motifs DPDxP and GIHR essential for anion-binding activity are highly conserved in PfPEBP. A large number of light-responsive elements were detected in promoter regions of PfPEBP. Gene expression of PfFT1 exhibited a diurnal rhythm. It was highly expressed in leaves under the short-day photoperiod, but higher in flowers and seeds under the long-day photoperiod. Overexpression of PfFT1 in Arabidopsis thaliana not only promoted early flowering of Col-0 or Ler, but also rescued the late flowering phenotype of ft-1 mutant. We concluded that PfFT1 promotes early flowering by regulating the expression of flowering-related genes AtAP1, AtLFY, AtFUL and AtSOC1. In conclusion, our results provided valuable information for elucidating the functions of PfPEBP in P. frutescens and shed light on the promoting effect of PfFT1 on flowering.